Decreasing financial imbalances or distorting competition? Examining the effects of the 50plus1-rule in German football - Oliver Budzinski; Philipp Kunz-Kaltenhäuser (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2025)
The so-called 50plus1-rule in German football is a controversially discussed institution that regulates the investment behavior of professional football teams. This paper provides an empirical analysis of its effects. We gathered panel data on 47 teams in the German Major League Football ("Erste Bundesliga") from the seasons 1989/90 until 2018/2019. This paper applies a Difference-in-Differences approach to examine investment behavior in budgets, as well as sporting success between impacted competitors and those exempted from the rule. Our results do not suggest any equalizing properties of the regulation. By contrast, we find anticompetitive effects and distorting properties of the current regulation.
Keywords: Z23; Z21; Z2; J83; L11; L50; 330; 50plus1-rule; football; sports economics; financial regulation; investment; sport finance; soccer; competition economics; sports antitrust